ANALISIS TAPER TANTRUM TERHADAP KINERJA KEUANGAN BANK UMUM SYARIAH DI INDONESIA - Shafira, Alfina; Muhajirin, Muhajirin; Prawiro, Atmo (Sekolah Tinggi Ilmu Fikih Syeikh Nawawi Tanara Serang, 2024)
The phenomenon of the financial crisis that occurred in 2008/2009 can be seen from the declining economic growth rate compared to the previous year, which was 4.6 percent. After the United States implemented a quantitative easing policy for 5 years, in 2013 the Fed again implemented a policy of tapering off or taper tantrums which caused the economy in several countries, especially India, Indonesia, Brazil, Turkey and Brazil to experience shocks. Islamic banks currently operate side by side with conventional interest-based banks, where the advantage appears to be more favorable to interest-based banks in terms of the secondary market and accessibility to loans as a last resort in difficult situations. So the conclusion that the author can draw is that the taper tantrum phenomenon that occurs does not always experience a decline in the equity market, especially in developing countries. Significant influence occurs in countries such as the People's Republic of China; Hong Kong, China; Republic of Korea; and Singapore.